Complex Meniscal Tear Repair With Meniscus Cap Implant: Technical Note - Kinga Ciemniewska-Gorzela, Ph.D.; Katarzyna Żak-Pałczyńska, M.D.; Radomir Henklewski, D.V.M., Ph.D.; James Murray; Marcin K. Waśko, M.D., Ph.D.; Justus Gille, M.D. (Arthroscopy Techniques, 2025)
Meniscal tears are prevalent injuries that significantly impact knee function and overall mobility. This technical note outlines our surgical technique using the Meniscus Cap implant, a composite device designed to enhance both biomechanical stability and support during meniscal repair. By integrating a collagen membrane with polycaprolactone filaments, the Meniscus Cap not only reinforces the meniscal structure but also provides exceptional mechanical properties. The unique structure of the Meniscus Cap improves load distribution and enhances the integrity of the surgical site, making it particularly beneficial for complex tears. This article details the surgical technique, implant characteristics, and potential technical advantages of this innovative approach.